Leafy Vegetables as Natural Sources of Minerals and Vitamins and Their Role in Human Health: A Review - Alhafadhi, Arshed; Alnassrallah, Rakhaa; Alobaidi, Ahmed; Almansarawi, Ali; Alshemari, Nada; Al-Salhi, Ahmed Ali Al-Salhi; Al-Shatty, Sabah (Indonesian Journal Publisher, 2025)
This review aims to assess the nutritional composition and health-promoting effects of selected leafy green vegetables—celery, basil, arugula, garden cress, and radish—and their potential contribution to preventing chronic diseases. Recent scientific evidence (2020–2025) was analyzed from clinical, epidemiological, and biochemical studies highlighting the physiological effects of these vegetables. The review methodology focused on identifying bioactive compounds, including nitrates, flavonoids, vitamins, and minerals, and evaluating their effects on key health outcomes such as cardiovascular performance, metabolic regulation, and digestive function. Results indicate that regular consumption of nitrate-rich leafy vegetables significantly contributes to lowering blood pressure, improving vascular elasticity, and reducing oxidative stress. Bioactive components such as flavonoids and polyphenols enhance lipid metabolism, decrease LDL cholesterol, and support antioxidant defense systems. Furthermore, dietary fiber and phytochemicals from arugula, celery, and basil positively influence gut microbiota composition and intestinal health, while compounds in radish and garden cress demonstrate glucose-regulating and anti-inflammatory properties.Overall, incorporating a diverse range of leafy green vegetables into daily diets serves as an effective, low-cost nutritional strategy to improve cardiovascular, metabolic, and digestive health. The findings underscore the need for further controlled clinical trials to determine optimal intake levels, synergistic effects among different species, and precise biochemical pathways underlying these health benefits.